Using reflective journal in ESL pre-service teacher education - Mat Nayan, Noor Fadhilah (2005)
The concept of reflective teaching has been an accepted approach in teacher education training for quite some time (Richards & Ho, 1998). Advocates of reflective teaching have reported that this approach has been effective in helping trainees become better teachers (Cruickshank et.al.l98l, Zeichner, 1987; Schon, 1987). One way to implement this approach into a teacher training programme is through journal writing or reflective journals. This paper will describe a study which attempted to investigate the role of journals in shaping the reflective process of pre service teachers in Malaysia. The main research questions were: l) to what extent were reflective journals an effective tool of growth in enhancing pre-service teachers to become more reflective. 2) to what extent did reflective journals provide insights into understanding complex concepts such as teachers’ beliefs and attitudes of teaching English in the Malaysian context. This paper will report the findings of this study. Instances from the journal entries will be analyzed and discussed. The primary source of data was from journal entries as well as observations and an interview. The participants involved were final year Teaching English as a Second Language (TESL) students in a Simulated Teaching (PBET3l03) course at the Education Faculty, University of Malaya.